Scaling Laws for Partially Developed Turbulence - Hsu, Abigail; Kaufman, Ryan; Glimm, James (Frontiers in Applied Mathematics and Statistics, 2022)
We formulate multifractal models for velocity differences and gradients which describe the full range of length scales in turbulent flow, namely: laminar, dissipation, inertial, and stirring ranges. The models subsume existing models of inertial range turbulence. In the localized ranges of length scales in which the turbulence is only partially developed, we propose multifractal scaling laws with scaling exponents modified from their inertial range values. In local regions, even within a fully developed turbulent flow, the turbulence is not isotropic nor scale invariant due to the influence of larger turbulent structures (or their absence). For this reason, turbulence that is not fully developed is an important issue which inertial range study can not address. In the ranges of partially developed turbulence, the flow can be far from universal, so that standard inertial range turbulence scaling models become inapplicable. The model proposed here serves as a replacement. Details of the fitting of the parameters for the $τ_p$ and $ζ_p$ models in the dissipation range are discussed. Some of the behavior of $ζ_p$ for larger p is unexplained. The theories are verified by comparing to high resolution simulation data.